Kinematic and Temporal Differences Between World-Class Men's and Women's Hurdling Techniques - Bissas, Athanassios; Paradisis, Giorgos P.; Hanley, Brian; Merlino, Stéphane; Walker, Josh (Frontiers in Sports and Active Living, 2022)
This study aimed to compare joint kinematics and center of mass parameters throughout hurdle clearance between world-class men and women sprint hurdlers, who were competing in a World Championships final. This was the first study to present time-series kinematic data around hurdle clearance, and given the technical ability of the athletes analyzed, it can be used as a template when analyzing the technique of other athletes in similar competitions and training. Video data were collected of the 16 finalists at the 2017 IAAF World Championships using four high-speed cameras (150 Hz). Video files were continuously digitized manually from touchdown before hurdle clearance to toe-off after landing around the sixth hurdle for men and the fifth hurdle for women, and sex-based comparisons were made at key discrete time points using independent t-tests, and throughout the entire hurdle phase using statistical parametric mapping. When calculated relative to hurdle height, the women’s center of mass height was significantly greater than the men’s throughout the full analyzed sequence (p < 0.001). Men also displayed more hip flexion in the lead leg at take-off before hurdle clearance (p = 0.029) as well as a more extended knee joint at intervals during flight and upon landing (p ≤ 0.037). Women completed the hurdle phase in a significantly shorter time than men ( 11% difference, p < 0.001). Finally, women seemed to be more efficient by maintaining and even exceeding their entry velocity for the first 40% of the hurdle phase. These results show a lower technical demand for the women to successfully negotiate hurdle clearance, thus providing further evidence to support the argument that the women’s hurdle height is too low for their performance capabilities and should be raised in senior competition.